Targeting Mitochondrial Oxidative Stress to Mitigate UV-Induced Skin Damage - Rhonda M. Brand; Rhonda M. Brand; Peter Wipf; Peter Wipf; Austin Durham; Michael W. Epperly; Joel S. Greenberger; Joel S. Greenberger; Joel S. Greenberger; Louis D. Falo; Louis D. Falo; Louis D. Falo; et al. (Frontiers Media S.A., 2018)
Unmitigated UV radiation (UVR) induces skin photoaging and multiple forms of cutaneous carcinoma by complex pathways that include those mediated by UV-induced reactive oxygen species (ROS). Upon UVR exposure, a cascade of events is induced that overwhelms the skin's natural antioxidant defenses and results in DNA damage, intracellular lipid and protein peroxidation, and the dysregulation of pathways that modulate inflammatory and apoptotic responses. To this end, natural products with potent antioxidant properties have been developed to prevent, mitigate, or reverse this damage with varying degrees of success. Mitochondria are particularly susceptible to ROS and subsequent DNA damage as they are a major intracellular source of oxidants. Therefore, the development of mitochondrially targeted agents to mitigate mitochondrial oxidative stress and resulting DNA damage is a logical approach to prevent and treat UV-induced skin damage. We summarize evidence that some existing natural products may reduce mitochondrial oxidative stress and support for synthetically generated mitochondrial targeted cyclic nitroxides as potential alternatives for the prevention and mitigation of UVR-induced skin damage.